Identification of resistant sources against bakanae disease in short grained aromatic rice (Oryza sativa) - S T, PRASHANTHA; YADAV, GAURAV KUMAR; S, GOPALA KRISHNAN; BASHYAL, BISHNU MAYA (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during rainy (kharif) seasons of 2019 and 2020 at the research farm of ICAR Indian Agricultural Research Institute, New Delhi to screen 90 genotypes of scented short grained rice (Oryza sativa L.) for Fusarium fujikuroi resistance. Genotypes Kankjeer A, Lectimanchi-A, Sumati, Pankhali-203, GR-102, NWGR- 3042, Geetanjali, R 1432-261-105-2-1-2, Khaskani, C-4-63-G, Calrose 76, JJ 92, Koliha, Hari Shankar, Kusuma, IR 74717-3-3-1-3, IR 74725-115-3-3-3, IR 74728-134-1-1-3, Hansraj, Anterved and GAR-1 were identified as moderately resistant with the disease rating of 3 in both the years of evaluation. Further, a set of genotypes with different disease response was evaluated for different parameters including root length, shoot length, number of fibres/threads in roots, days of symptom appearance and area under disease progress curve (AUDPC). Disease severity was observed to be significantly correlated (r = 1.0) with AUDPC and days required for the symptom appearance (r = 0.95). Results indicated that apart from the disease severity, AUDPC could also be considered as a one of the component for the bakanae disease resistance. The resistant sources identified in the present study can be utilized in rice breeding programme against bakanae disease.